2008
DOI: 10.4269/ajtmh.2008.79.353
|View full text |Cite
|
Sign up to set email alerts
|

An Envelope Domain III–based Chimeric Antigen Produced in Pichia pastoris Elicits Neutralizing Antibodies Against All Four Dengue Virus Serotypes

Abstract: There is currently no vaccine to prevent dengue (DEN) virus infection, which is caused by any one of four closely related serotypes, DEN-1, DEN-2, DEN-3, or DEN-4. A DEN vaccine must be tetravalent, because immunity to a single serotype does not offer cross-protection against the other serotypes. We have developed a novel tetravalent chimeric protein by fusing the receptor-binding envelope domain III (EDIII) of the four DEN virus serotypes. This protein was expressed in the yeast, Pichia pastoris, and purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 57 publications
0
43
0
1
Order By: Relevance
“…When expressed in Pichia pastoris, the tetravalent fusion protein linking the EDIII domains of the four dengue virus serotypes has already been reported to elicit neutralizing antibodies against all four serotypes (Batra et al 2007;Etemad et al 2008). Although, the plantderived recombinant proteins are required to undergo separate and independent evaluations regarding immunogenicity, the outcome of such studies is expected to be very similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When expressed in Pichia pastoris, the tetravalent fusion protein linking the EDIII domains of the four dengue virus serotypes has already been reported to elicit neutralizing antibodies against all four serotypes (Batra et al 2007;Etemad et al 2008). Although, the plantderived recombinant proteins are required to undergo separate and independent evaluations regarding immunogenicity, the outcome of such studies is expected to be very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Since the main target group for a dengue vaccine are the relatively poor people in developing countries, the ideal dengue vaccine should be affordable, heat-stable (i.e., independent of an uninterrupted cooling chain) and easy to administer. Recombinant dengue virus EDIII protein-based antigens have been previously expressed in E.coli (Khanam et al 2006;McDonald et al 2009;Simmons et al 1999;Srivastava et al 2000;Tripathi et al 2008Tripathi et al , 2011Zhao et al 2014), in yeast (Arora et al 2013;Batra et al 2010a;Cardoso et al 2013;Etemad et al 2008;Nguyen et al 2015), in insect cells (Ivy et al 2000) and also via nuclear transformation in plants (Kim et al 2013;Martinez et al 2010;Saejung et al 2007). In the present study, the dengue virus envelop protein domain III-based tetravalent fusion protein (EDIII-1-4) and the monovalent forms (EDIII-1, EDIII-3 and EDIII-4) have been expressed in tobacco chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] In this study, we cloned the EIII gene into pQE30-Xa expression vector and the expression of the recombinant EIII protein in E. coli XL1-Blue MRF′ was chemically induced with IPTG. SDS-PAGE analyses of the protein profiles demonstrated that recombinant EIII protein expression was optimal at approximately 4-5 h post-IPTG induction at 37°C.…”
Section: Resultsmentioning
confidence: 99%
“…Other laboratories have established high-yield expression systems for EPs of JEV or West Nile virus using the mammalian cell lines COS-1 (5, 15), RK-13 (24,43), and CHO-K1 (52). In addition to mammalian cells, bacterial (2,42,54,57), yeast (7,8,38), and insect (23,36,48,51,56) cells have been used to produce flavivirus vaccine candidates; most of these studies have focused on a truncated E protein or domain III of the E protein. These vaccine candidates were able to induce neutralizing antibodies and/or protection in animals.…”
Section: Discussionmentioning
confidence: 99%